Diseminasi Standar Makanan, Pengolahan Jus Varian Buah dan Sayur Serta Edukasi Kepada Lansia Hipertensi Di Panti Sosial Tresna Werdha Budi Sejahtera Banjarbaru - Rijanti Abdurrachim; Niken Widyastuti Hariati; Endang Sri Purwanti Ningsih (Jurnal Abdimas Kesehatan (JAK), 2022)
Elderly is an age group that is very vulnerable to suffer from hypertension. In addition to medication, blood pressure can be controlled by managing diet and giving fruits and vegetables. The Community Service Team carried out dissemination of food standards, processing of fruit and vegetable variant juices and education for the elderly with hypertension at the Tresna Werdha Budi Sejahtera Social Home Banjarbaru. The purpose of the activity is to provide input to nursing home managers regarding food standards, training and demonstrations of making fruit and vegetable juice variants as well as providing knowledge about eating arrangements for controlling blood pressure in the elderly. Method: Phase I: Dissemination to the management and health workers regarding food standards for the elderly with hypertension. Phase II: Conducting demonstrations of making fruit and vegetable variant juices and training nutritionists and health workers. Phase III: educating the elderly about eating arrangements and measuring blood pressure. The results of the activity: I. The results of the dissemination of suggestions for improving food standards for the elderly in order to control the blood pressure of the elderly at the Tresna Werdha Home., II The results of the juice making demonstration and training: the health workers were very enthusiastic, starting from the explanation from the preparation process to the making process. The results of education and blood pressure examinations found high grade 1 and 2 hypertension conditions. It is not possible to do pre and post-tests to explore the level of knowledge in the elderly. Asking questions directly from what is explained, all the elderly can answer. The preparation of food standards for the elderly with the addition of a composition of vegetables and fruit, the proposal to enter a joint juice drinking program with the elderly, providing continuous mentoring and motivation by nutritionists, are opportunities for the implementation of the MOU/cooperation agreement with the Social Institution.